Effects of Leverage, Size, ROA, GDP on Firm Value: Indonesia Automotive & Allied 2022–2024 - Ade Suryana; Jana Sandra; Muhammad Iqbal Firdaus (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the effects of Financial Leverage, Firm Size, Return on Assets (ROA), and Gross Domestic Product (GDP) on firm value among Automotive & Allied Products issuers listed on the Indonesia Stock Exchange during 2022–2024. Data from 10 companies (N = 30 firm-years), sourced from ICMD and financial reports, were analyzed using panel data regression. Based on Chow, Hausman, and Lagrange Multiplier tests, the Random Effects Model (REM) was selected. Results show that GDP significantly and positively influences firm value (β = 0.016750; p = 0.0206), while leverage, firm size, and ROA do not show significant effects. The joint F-test is also insignificant (F = 1.531921; p = 0.223398) with an Adjusted R² of 0.068353. These findings suggest that macroeconomic factors play a more dominant role in valuing cyclical sectors like automotive, compared to short-term firm-specific indicators. Managerial implications include adopting cycle-sensitive planning, enhancing cash flow resilience, and cautious debt and scale management. This study contributes post-pandemic insights to emerging-market literature and recommends future research with broader timeframes, dynamic models, and additional variables to address endogeneity and improve result robustness.